Dematerialisation of workplace in non-classical labour law relations - Mélypataki, Gábor (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
New atypical forms of employment need to be examined in terms of how they differ from classic labour law. One such significant difference is the location of work. In the case of telework and home office, we usually talk about working at home, which means the privatization of jobs. From here on, application-based work is a further step, which means the full dematerialization of jobs. But the dematerialisation of jobs does not mean that we cannot talk about employment.